PENGARUH KEMISKINAN, TINGKAT PENGANGGURAN DAN TINGKAT PENDIDIKAN TERHADAP IPM DI KABUPATEN/KOTA PROVINSI BALI 2014-2019 - Febrianti, Uli Mutia; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Human Development Index (HDI) measures human welfare in terms of three indicators, namely Health, Education, and Standards of Living. The purpose of this study was to determine the effect of poverty, unemployment rate and education level partially and simultaneously on HDI in the Regency/City of Bali Province in 2014-2019. This research was conducted in all regencies/cities of Bali Province using secondary data from the Bali Province Central Statistics Agency with the method of collecting data by non-participant observation and the analysis technique used was Multiple Linear Regression with a total of 54 observations from 8 regencies and 1 city. in Bali Province within 6 years. The results showed that poverty, unemployment rate and education level simultaneously had a positive and significant effect on HDI, while the partial study of poverty and unemployment variables had a negative effect on HDI, while the education level variable had a positive effect on poverty in the Regency/City of Bali Province in 2014. -2019.   Keywords: Poverty, Unemployment Rate, Education Level, Human Development Index.